Attitude and position measurement of bit for underwater horizontal directional drilling system. (1st September 2016) - Yang, Ke; Ge, Tong; Wang, Xuyang
Abstract: In order to solve the problem of attitude and position measurement of bit, a new navigation algorithm was developed based on nonholonomic constraints and steady-state component constraints. The state error propagation model based on random walk of sensors was deduced. Underwater horizontal directional drilling system has two states: drilling and static. In the drilling state, the velocity of bit in the plane perpendicular to the forward direction is almost zero (nonholonomic constraints), and the steady-state component of acceleration and angular velocity of bit does not exist (steady-state component constraints). In the static state, velocity, acceleration, angular velocity, and the steady-state component of acceleration and angular velocity are equal to zero. So, the information of nonholonomic constraints and steady-state component constraints can be integrated with navigation algorithm by indirect Kalman filter based on state error propagation model. IMU7200 mounted in the bit can provides measurement of acceleration and angular velocity of bit. The encoder mounted in the injection head (encoder 1) can provide measurement of velocity of bit. The encoder mounted in the coil winch (encoder 2) can be used to discover slippage between coiled tubing and the shaft of injection head. The experimental results show that the navigation algorithm proposed in this paper can realize accurate measurement of attitude and position of bit. Highlights: We solve the problem of attitude and position measurement of bit of UHDD. We propose a navigation algorithm to provide attitude and position information of bit. The state error propagation model based on random walk of sensors was deduced. The constraints information was integrated with navigation algorithm by indirect Kalman filter. The experimental results show the validity of navigation algorithm proposed in this paper.